2004
DOI: 10.1074/jbc.m311612200
|View full text |Cite
|
Sign up to set email alerts
|

Gs Protein-coupled Receptor Agonists Induce Transactivation of the Epidermal Growth Factor Receptor in T84 Cells

Abstract: We have previously shown that G q protein-coupled receptor (G q PCR) agonists stimulate epidermal growth factor receptor (EGFr) transactivation and activation of mitogen-activated protein kinases (MAPK) in colonic epithelial cells. This constitutes a mechanism by which Cl ؊ secretory responses to G q PCR agonists are limited. In the present study we examined a possible role for the EGFr in regulating Cl ؊ secretion stimulated by agonists that act through G s PCRs. All experiments were performed using monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 59 publications
5
32
1
Order By: Relevance
“…The A 1 -mediated chloride current induced by luminal adenosine might involve a similar mechanism because in airway epithelial cells, A 1 agonists activate chloride secretion via mobilization of intracellular calcium (35). Other mechanisms also deserve consideration in light of the recent elegant studies of the group of Barrett and colleagues (2,19), who established that transactivation of the EGF receptor (EGFR) is a new mechanism controlling intestinal chloride secretion with downstream effectors involving either phosphatidylinositol 3-kinase (PI3-kinase) or MAPK. For instance, the full chloride secretory response to VIP in T84 monolayers involves activation of PI3-kinase through EFGR transactivation by a typical G scoupled receptor (2).…”
Section: Discussionmentioning
confidence: 99%
“…The A 1 -mediated chloride current induced by luminal adenosine might involve a similar mechanism because in airway epithelial cells, A 1 agonists activate chloride secretion via mobilization of intracellular calcium (35). Other mechanisms also deserve consideration in light of the recent elegant studies of the group of Barrett and colleagues (2,19), who established that transactivation of the EGF receptor (EGFR) is a new mechanism controlling intestinal chloride secretion with downstream effectors involving either phosphatidylinositol 3-kinase (PI3-kinase) or MAPK. For instance, the full chloride secretory response to VIP in T84 monolayers involves activation of PI3-kinase through EFGR transactivation by a typical G scoupled receptor (2).…”
Section: Discussionmentioning
confidence: 99%
“…At this time there is no implication of the involvement of other G proteins in NT signaling in NCM460 cells. Because G proteins including G s (45), G i (28, 40), G q/11 (46,47), and G 13 (48) have been shown to mediate transactivation of the EGF receptor, further studies are needed to identify which G protein(s) mediates EGF receptor transactivation and to determine the signaling molecules involved in this NT response.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that transactivation of the epidermal growth factor receptor (EGFR) reduces the extent of G q -protein coupled receptor induced Cl -secretion while increasing secretory responses mediated by G s -protein coupled receptors in colonic epithelial cells [24,25]. Recent evidence has also suggested EGFR can be transactivated by steroid hormones in a nongenomic fashion [26][27][28][29].…”
Section: Signaling Pathways Involved In the Antisecretory Response Tomentioning
confidence: 99%